HOW AI-DRIVEN GAMIFICATION IS RESHAPING HIGHER EDUCATION CLASSROOMS (SCIENCE TIME JOURNAL, 2026)
This article explores the transformative role of AI-driven gamification in higher education. Traditional lecture-based teaching often struggles to maintain student engagement in the face of distractions and diverse learning needs. By integrating game design elements–such as points, badges, leaderboards, challenges, and narratives–with artificial intelligence, educators can create dynamic, personalized, and adaptive learning experiences. AI enhances gamification through real-time content generation, performance-based adaptation, immediate personalized feedback, and automated assessment, making learning more motivating and effective.